Subcutaneous Panniculitis-like T-cell Lymphoma - Sonal Mandli; Rutu Harsh Oza; Amita H Sutaria; Bela J Shah (Wolters Kluwer Medknow Publications, 2024)
Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a primary, rare cutaneous T-cell lymphoma that resembles panniculitis and accounts for <1% of all peripheral T-cell lymphomas. It is characterized by multiple subcutaneous nodules and plaques, which usually involve the extremities. Histopathological findings include the presence of neoplastic T-cell surround and disrupt individual adipocyte membranes. Immunohistochemistry will confirm diagnosis by CD8+ and CD56− cells. Here, we report a case of a 29-year-old female who presented with cutaneous panniculitis-like lesions diagnosed with cutaneous T-cell lymphoma with the help of histopathology and immunohistochemistry.